Representações culturais na Bienal de Artes Visuais do Mercosul: o estatuto da fotografia e a expressão do sujeito social - Luz, Patricia Camera Varella da (2012)
This thesis investigates the representation of cultural identity at Mercosul Biennial. The object of study is the photo essay Sangre, made by argentine Diego Levy, and the photo essay Fin de Zone Urban, made by paraguayan Carlos Bittar. These essays are printed in catalogue (Mercosul Biennial, 2003). The aim is analyze the four editions of BAVM (1997-2003), the photography and the modern subject. Based on investigation about identity, developed by Néstor García Canclini, Anthony Giddens and fundamentally Alain Touraine, this research affirms that the individual lives the estrangement between the State and the subject. Considering this context, this thesis argues that cultural identities are represented in these photo essays together to the process of making multiple territories. The main line of this interpretation is based on the theory about the dynamics of new territorialities developed by Rogério Haesbaert. Through the investigation developed by André Rouillé, this research understands that the photo essays were obtained by the praxis of photography-expression. This thesis recognized that the Mercosul Biennial is historic place. The photographer and the person photographed are associated as social actors.